2009
DOI: 10.1590/s1678-77572009000500017
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Aggregatibacter actinomycetemcomitans in Brazilian indians from Umutina Reservation, Mato Grosso, Brazil

Abstract: A ggregatibacter actinomycetemcomitans is associated with periodontal disease, especially localized aggressive periodontitis, produces a potent leukotoxin and its distribution is influenced by ethnic characteristics of the population.Objective:Using culture and polymerase chain reaction (PCR) techniques, this study evaluated the occurrence of this microorganism and the distribution of leukotoxic strains isolated from Indians belonging to the Umutima Reservation, Mato Grosso, Brazil.Material and Methods:Forty-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…Meanwhile, A. actinomycetemcomitans and Tannerella forsythia were not reliably detected by sampling either saliva or periodontal pockets. Other studies also found that a salivary sample alone did not identify all individuals infected with A. actinomycetemcomitans . From these results, Slots & Slots have reviewed that saliva seems to be superior to periodontal pocket samples for detecting P. gingivalis , P. intermedia , P. nigrescens and T. denticola , but reasonably good accuracy may be necessary for detection of A. actinomycetemcomitans and T .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, A. actinomycetemcomitans and Tannerella forsythia were not reliably detected by sampling either saliva or periodontal pockets. Other studies also found that a salivary sample alone did not identify all individuals infected with A. actinomycetemcomitans . From these results, Slots & Slots have reviewed that saliva seems to be superior to periodontal pocket samples for detecting P. gingivalis , P. intermedia , P. nigrescens and T. denticola , but reasonably good accuracy may be necessary for detection of A. actinomycetemcomitans and T .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, such variations in the global distribution of periodontopathic bacteria could be important in the epidemiology and the treatment of periodontal diseases. In view of the limited data available on the Brazilian distribution of A. actinomycetemcomitans in chronic periodontitis subjects 5,7,22,23 and as this bacterium was also considered a true pathogen, we examined the occurrence of A. actinomycetemcomitans in Brazilian subjects with mild, moderate and severe chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an interesting study was conducted by Vieira et al 23 (2009) in native Brazilians. The authors included 38 patients with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Cortelli et al, (2005) recommended that serotype b be used as a diagnostic marker for aggressive periodontitis since they found a high prevalence of the JP2 clone in a Brazilian population. These findings have been contradicted by other studies on Brazilians which showed very low, if any, serotype b strains (Vieira et al, 2009;Roman-Torres et al, 2010). Yet another study showed similar frequencies of serotypes b and c but associated serotype b with health and c with disease (Teixeira et al, (2006).…”
Section: Gene Expressionmentioning
confidence: 60%
“…Yet another study showed similar frequencies of serotypes b and c but associated serotype b with health and c with disease (Teixeira et al, (2006). The contradictions in these results may be due to the fact that Brazil has a multi-ethnic population of predominantly African and Mediterranean origin, while the native Brazilians, descending from almost extinct ethnic groups who live in cultural isolation with no mixing with other ethnic groups (Vieira et al, 2009), have not been exposed to the toxic strains of Aa.…”
Section: Gene Expressionmentioning
confidence: 95%